Broodstock development in freshwater prawn Macrobrachium rosenbergii by artificial insemination - Bhaskar, N Vijaya; Mariappan, S; Surendraraj, A; Venkataramani, V K (Indian Journal of Fisheries, 2011)
Broodstock development in freshwater prawn Macrobrachium rosenbergii by artificial insemination